Dental caries-related quality of life and socioeconomic status of preschool children, Bauru, SP - Angela Xavier; Fábio Silva de Carvalho; Roosevelt da Silva Bastos; Magali de Lourdes Caldana; José Roberto de Magalhães Bastos (Universidade Estadual de Campinas, 2015)
Aim: To evaluate oral health-related quality of life of preschool children of Bauru, State of São Paulo, Brazil, and associate it with socioeconomic profile of households. Methods: The sample consisted of 229 preschool children between 3 and 5 years and the dmft (decayed, missing due to caries, filled teeth) index was adopted for assessment children's dental caries in accordance with the standards recommended by the World Health Organization. Questionnaires were used for evaluation oral health-related quality of life (Early Childhood Oral Health Impact Scale) and socioeconomic profile of parents or guardians of the preschool children. Statistical analysis was performed descriptively by relative and absolute frequencies and by Spearman's correlation and Kruskal-Wallis test (p <0.05). Results: A dmft of 1.65 (± 2.87) and a Sic Index 4.88 (± 3.20) were found, indicating the polarization of dental caries in the studied group. It was verified low influence of oral health on quality of life of the children examined. With respect to socioeconomic classification, 66.38% of families were in the lower middle class. Linear and statistically significant correlation was found between dmft and oral health-related quality of life for the overall score and domains of the questionnaire (p<0.001). Conclusions: It was found low influence of oral health on quality of life of the preschool children and the assessment of socioeconomic conditions of the children's families may guide practices aiming to reducing inequalities in the distribution of dental caries in the population.